Genomic characterization and probiotic assessment of Bifidobacterium breve JKL2022 with strain-specific CLA-converting properties - Arxel G. Elnar; Byeonggwan Eum; Geun-Bae Kim (Scientific Reports)
Abstract Bifidobacterium breve is a well-recognized probiotic species. B. breve JKL2022, a strain isolated from the feces of healthy infants that exhibits superior conjugated linoleic acid (CLA)-converting activity, was functionally characterized for probiotic safety and applicability through genomic and in vitro analyses. The JKL2022 genome comprises a 2,313,948 bp sequence assembled into a single contig, encoding a total of 1,998 genes. In silico predictive analyses confirmed the absence of virulence factors and acquired resistance genes while verifying its intrinsic antimicrobial resistance profile. Several CAZymes were identified, consistent with the strain’s fermentation profile. Additionally, the gene encoding the key enzyme for CLA conversion was identified as a 993-bp lai gene, underscoring the species-level differences in microbial CLA metabolism. The functionality, stress tolerance, and safety of JKL2022 were further confirmed through experimental assessments. JKL2022 exhibited tolerance to acid and bile salts, auto-aggregation, and cell surface hydrophobicity, indicating its potential to survive gastrointestinal transit. Furthermore, JKL2022 exhibited α-glucosidase inhibitory activity and tested negative for starch hydrolysis, hemolysis, and gelatinase activity. The inherent probiotic properties of Bifidobacterium, combined with the strain-specific CLA conversion using growing cells and postbiotic preparations, contribute to the potential health benefits of B. breve JKL2022, as verified in this study.